2017
DOI: 10.1002/jca.21546
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study comparing tryptophan immunoadsorption with therapeutic plasma exchange for the treatment of chronic inflammatory demyelinating polyneuropathy*

Abstract: The results of this pilot study suggest that IA is at least equally effective and safe compared to PE in CIDP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
0
19
0
3
Order By: Relevance
“…The authors reported a similar rate of clinical improvement and side effects, and this is in line with retrospective studies indicating that there is little difference between the two treatments. 65 Immunosuppression may be required particularly in atypical CIDP variants or in long-term cases, using agents such as azathioprine, mycophenolate mofetil or methotrexate, although evidence from randomised controlled trials is lacking for these agents. A randomised controlled study that evaluated the utility of fingolimod in CIDP did not show any beneficial effect and was stopped for futility.…”
Section: Treatmentmentioning
confidence: 99%
“…The authors reported a similar rate of clinical improvement and side effects, and this is in line with retrospective studies indicating that there is little difference between the two treatments. 65 Immunosuppression may be required particularly in atypical CIDP variants or in long-term cases, using agents such as azathioprine, mycophenolate mofetil or methotrexate, although evidence from randomised controlled trials is lacking for these agents. A randomised controlled study that evaluated the utility of fingolimod in CIDP did not show any beneficial effect and was stopped for futility.…”
Section: Treatmentmentioning
confidence: 99%
“…It was found that four patients (44.4%) in the TPE group responded to treatment compared to six patients (66.7%) in the IA group. In the IA group, 100% of the patients had an improvement in their MRC sum scores and four patients out of six patients (66.7%) [162].…”
Section: Chronic Inflammatory Demyelinating Polyradiculoneuropathymentioning
confidence: 96%
“…Immunoglobulins can be targeted for removal through binding to selected ligands on the backing matrix surface (membranes or beads) of the adsorption column (Table II). Although IA is effective for the treatment of pemphigus vulgaris 70,71 and CIDP, 72,73 IA systems are used less frequently than PLEX for the treatment of IgG autoantibody-mediated diseases, due to the availability and complexity of the procedure, and regulatory and economic differences between health care systems. 51 The American Society for Apheresis, the American Academy of Neurology, and other organizations have published guidelines and commentaries for PLEX and IA, 51,74,75 noting that side effects and complications of PLEX and IA mostly relate to the procedure itself.…”
Section: What Can We Learn From Other Conditions and Therapies? Procementioning
confidence: 99%